2016
DOI: 10.1098/rstb.2015.0530
|View full text |Cite
|
Sign up to set email alerts
|

What can we infer about the origin of sex in early eukaryotes?

Abstract: One contribution of 15 to a theme issue 'Weird sex: the underappreciated diversity of sexual reproduction'. Current analysis shows that the last eukaryotic common ancestor (LECA) was capable of full meiotic sex. The original eukaryotic life cycle can probably be described as clonal, interrupted by episodic sex triggered by external or internal stressors. The cycle could have started in a highly flexible form, with the interruption of either diploid or haploid clonal growth determined by stress signals only. Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0
13

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 107 publications
(144 reference statements)
0
31
0
13
Order By: Relevance
“…During meiosis, homologous chromosomes are aligned allowing for recombination and silencing of newly translocated selfish elements . As meiosis promotes a large‐scale repair of the nuclear genome, it was suggested that meiosis evolved and was maintained as a way to repair the genome from continuous DNA damage caused by increased amounts of reactive oxygen species generated by mitochondrial metabolism …”
Section: Introductionmentioning
confidence: 99%
“…During meiosis, homologous chromosomes are aligned allowing for recombination and silencing of newly translocated selfish elements . As meiosis promotes a large‐scale repair of the nuclear genome, it was suggested that meiosis evolved and was maintained as a way to repair the genome from continuous DNA damage caused by increased amounts of reactive oxygen species generated by mitochondrial metabolism …”
Section: Introductionmentioning
confidence: 99%
“…The anisogamy is a result of conflicts inside zygote between mitochondria from cytoplasms of two gamets, which favored the selection for one large ovum exclusively containing mitochondria for future zygote as a gamete for female sex and multiple competing small mitochondria-less sperms as gametes for male sex. Moreover meiosis itself -the evolutionary benefit outweighing the two-fold cost of sex -might have originated as a response to symbiogenesis [76].…”
Section: Other Major Transitionsmentioning
confidence: 99%
“…Sex in the classical sense is not the only way to swap genes [3], so why do so many organisms insist on a complex cocktail of the four features of meiotic sex [4]? Sex is very often facultative rather than obligate, yet the organisms most familiar to us are mostly obligatorily sexual [5].…”
mentioning
confidence: 99%
“…The topics addressed in this special issue range from very fundamental questions such as the evolutionary benefits [12] and the origin of sex [3,4,13] and mating types [6], to secondary consequences of sexual reproduction, such as sexual selection [5,11] and the increased scope for genetic conflict [8,10,14], and the cost of sex, either due to the production of males in anisogamous species or due to mate finding or mechanisms of meiosis [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation